2013
DOI: 10.1073/pnas.1317643111
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella exploits NLRP12-dependent innate immune signaling to suppress host defenses during infection

Abstract: The nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing 12 (NLRP12) plays a protective role in intestinal inflammation and carcinogenesis, but the physiological function of this NLR during microbial infection is largely unexplored. Salmonella enterica serovar Typhimurium (S. typhimurium) is a leading cause of food poisoning worldwide. Here, we show that NLRP12-deficient mice were highly resistant to S. typhimurium infection. Salmonella-infected macrophages induced NLRP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 34 publications
3
130
1
1
Order By: Relevance
“…However, recent work of Zaki et al identified a contrary role of NLRP12 in S. Tm infections. Here, NLRP12-deficient mice were hyperresistant to S. Tm, and NLRP12 was identified as a suppressor of S. Tm-induced proinflammatory reactions (116). In line with this observation, NLRP12 was also reported as a suppressor of gastrointestinal inflammation upon DSS treatment and of tumorgenesis in an AOM/DSS cancer model by negative regulation of NF-B and AKT signaling (2,117).…”
Section: Nlrp12supporting
confidence: 54%
“…However, recent work of Zaki et al identified a contrary role of NLRP12 in S. Tm infections. Here, NLRP12-deficient mice were hyperresistant to S. Tm, and NLRP12 was identified as a suppressor of S. Tm-induced proinflammatory reactions (116). In line with this observation, NLRP12 was also reported as a suppressor of gastrointestinal inflammation upon DSS treatment and of tumorgenesis in an AOM/DSS cancer model by negative regulation of NF-B and AKT signaling (2,117).…”
Section: Nlrp12supporting
confidence: 54%
“…This result indicates that DWV infection could have a negative effect on NF-κB activation by enhancing the transcription of its negative modulator Amel\LRR. The possibility that DWV adopts a virulence strategy somewhat similar to that recently described for Salmonella, which targets an NLR protein that negatively regulates NF-κB signaling (31), is an intriguing hypothesis meriting further research efforts.…”
Section: Dwv Infection and Honey Bee Immunosuppressionmentioning
confidence: 93%
“…NLRP12 functions as a negative regulator of inflammation by modulating elements of the NF-k B signalling pathway ( Fig. 3) (Allen et al, 2012a, b;Arthur et al, 2007;Lei et al, 2012Lei et al, , 2013Moore et al, 2008;Tsuchiya et al, 2010;Wagner et al, 2009;Xia et al, 2011;Zaki et al, 2014). This hypothesis is supported by recent in vivo studies utilizing Nlrp12 2/2 mice in models of acute colitis and colitis-associated tumorigenesis.…”
Section: Nlrx1 Negatively Regulates Diverse Aspects Of Host Antiviralmentioning
confidence: 80%